Southern California marine protected areas promote bolder fish populations - Himes, Lucian; La Valle, Florybeth Flores (Frontiers in Marine Science, 2023)
Marine protected areas (MPAs) aim to protect habitats and ecosystems to promote the diversity and health of marine populations. To evaluate the health of fish populations within and outside of MPAs in Southern California, we used flight initiation distance (FID). FID is the distance at which an individual will flee from a perceived predator and is a direct measure of boldness. Lower FIDs are indicative of bolder populations. Lower FID values indicate that fish will have the opportunity to dedicate less energy to fleeing from predators which could then be used for increased foraging. Data was collected from eight locations along the Southern California coast, four in protected areas and four in non-protected areas. FIDs were measured with a sonar-based range finder. All fish species that recreational fishermen could catch were targeted, with a focus on six core species spearfishermen catch commonly. Results showed that all fish sampled in MPAs have significantly lower FIDs than those in non-protected areas. An ANOVA showed no significant difference between different locations of the same protected status. The six core species had lower average FIDs in protected areas, three species had significant differences between protected and non-protected populations, and there was no significant difference in FIDs between species. These results show that Southern California MPAs are promoting healthier fish communities with respect to boldness behavior. This data and methods can be implemented in future projects to expand the range of metrics measured to inform management tools for California’s MPAs and MPAs at large.